Penggunaan Kata Salam Perpisahan (Wakare no Aisatsu) Ditinjau dari Segi Sosial dan Budaya pada Masyarakat Jepang - Rusdi '; Arza Aibonotika; Zuli Laili Isnaini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract:. Abstract: Wakare no aisatsu (goodbye) in use in the daily life by the people of Japan are used when the speaker wants to end a meeting of the partners. The purpose of this study was to identify the factors that influence social and cultural use of wakare no aisatsu such as age, gender, and superior subordinate relationship (jouge kankei). In addition to knowing the forms wakare no aisatsu commonly used by people in Japan. The research method used is descriptive and analytical study of literature. In analyzing the data, the writer uses a few theories are considered to support the issues raised in this paper as the use of wakare no aisatsu is seen from the viewpoint at the level of formality, superior subordinate relationship (jouge kankei) and gender. The results of this study indicate that the use of wakare no aisatsu highly influenced by the level of formality and relationship between the speaker and partners. While gender tended to be neutral and there is no influence in its use. In general, Japanese women will typically use more polite language than men, both of the partners said higher position or below. While in terms of social and cultural, wakare no aisatsu important role in keeping the values that exist in the social life of the Japanese people.Key Word: Wakare, Aisatsu, Social, Cultural